2006
DOI: 10.1021/pr0603405
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Host Defence Proteins in Milk Using a Proteomic Approach

Abstract: Besides providing nutrition to the newborn, milk also protects the neonate and the mammary gland against infection. As well as the six major proteins, bovine milk contains minor proteins, not all of which have been characterized. In this study, we have subjected bovine skim milk, whey, and milk fat globule membrane (MFGM) fractions to both direct liquid chromatography-tandem mass spectrometry (LC-MS/MS), and two-dimensional electrophoresis (2-DE) followed by matrix assisted laser desorption ionization-time-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
248
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(274 citation statements)
references
References 53 publications
20
248
1
3
Order By: Relevance
“…In particular, specific histones have been identified on LDs purified from a number of mammalian cell lines and tissues (Smolenski et al, 2007; Wan et al, 2007; Zhang et al, 2011; Larsson et al, 2012). Thus, this defense system may be widely conserved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, specific histones have been identified on LDs purified from a number of mammalian cell lines and tissues (Smolenski et al, 2007; Wan et al, 2007; Zhang et al, 2011; Larsson et al, 2012). Thus, this defense system may be widely conserved.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, proteomic studies have revealed histones on LDs in tissues from larval and adult insects as well as in a range of mammalian cells (Smolenski et al, 2007; Wan et al, 2007; Yang et al, 2010; Zhang et al, 2011; Larsson et al, 2012), including mouse liver (Figure 6). Such a role of droplets in the antibacterial response may in part explain why the number and size of LDs increase in disease, from osteoarthritis to liver degeneration and cartilage overproliferation (Tilney and Portnoy, 1989; Bielecki et al, 1990; Lowder et al, 2000; Gunjan and Verreault, 2003; Figueredo et al, 2009; Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The secretory products of the mammary gland represent the expression of a large number of genes that are upregulated during lactation, but many of these products remain unknown (except as genes) or their functionalities are poorly understood (Smolenski et al, 2007;Lemay et al, 2009). Comparisons of monotreme, marsupial and eutherian genomes suggest that milk and mammary genes tend to be conserved, that is, have not diverged as much as other genes (Lemay et al, 2009).…”
Section: The Evolution Of Milk Constituentsmentioning
confidence: 99%
“…The prospect of using APPs as biomarkers of inflammation and infection for veterinary applications has inspired a significant body of research, including the development of antibodies and other quantitative methods for analyzing APP expression during disease in food animal species (Murata et al, 2004). More recently, interest in APPs as potential veterinary biomarkers has led to the application of proteomic strategies for the evaluation of APPs and measures of the host response in complex biological samples (Bendixen et al, 2011;Boehmer et al, 2010;Danielsen et al, 2010;Smolenski et al, 2007).…”
Section: Acute Phase Proteins: Biomarkers Of Infection and Inflammatimentioning
confidence: 99%
“…Proteomics has also been applied to the study of the gastrointestinal tract in swine (Wang et al, 2009;Danielsen et al, 2007Danielsen et al, , 2006, as well as dietinduced fatty liver disease in Ossabaw pigs . Studies aimed at the elucidation of potential biomarkers of bovine mastitis have specifically dominated veterinary biomarker initiatives in cattle, however, due in large part to affiliated inflammation, economic and food safety concerns, and the lack of efficacious treatment options (Boehmer et al, 2010;Danielsen et al, 2010;Smolenski et al, 2007;Hogarth et al, 2004). Several comparative proteomic studies have focused on the identification of diagnostic biomarkers of mastitis in bovine milk, though the proteomic analysis of mammary tissue from healthy cows and cows with clinical mastitis has also been conducted (Yang et al, 2009).…”
Section: Post-translational Modificationsmentioning
confidence: 99%